THE INFLUENCE OF FINTECH SELF-EFFICACY AND ATTITUDE ON INVESTMENT DECISIONS OF MUSLIM INVESTORS IN MALAYSIA - Che Hassan, Norhazimah; Abdul-Rahman, Aisyah; Ab. Hamid, Siti Ngayesah; Mohd Amin, Syajarul Imna (I-iECONS e-proceedings, 2023)
This study aims to identify the predictors of Islamic unit trust funds (IUT) investment intention from the investors' perspective. Additionally, this paper examines the moderating effect of fintech self-efficacy (FSE) on the relationship between attitude and investment intention. A total of 392 data were collected from IUT investors in Malaysia and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings reveal that subjective norms have the highest impact on investment intention, followed by attitude and FSE, while religiosity is not significantly associated with investment intention in Islamic unit trust funds. Attitude significantly mediates religiosity-intention and Islamic financial literacy-intention relationships. Additionally, FSE significantly moderates the relationship between attitude and investment intention. The results shed light on the key factors that increase investing behavior and have direct managerial implications with regard to marketing strategies and target markets. These findings suggest that IUT service providers should take the lead in attracting customers through effective and targeted marketing initiatives, particularly by enhancing customers' FSE and capabilities. This study provides empirical evidence on the interrelationships between IFL, religiosity, and FSE in examining investors' behavior using the Theory of Planned Behavior (TPB) framework. The role of perceived behavioral control was substituted with FSE. The study explores the moderating role of FSE on the relationship between attitude and investment intention.